Image Encryption and Decryption Using Chua’s Circuits - Alsaedi, Mohammed Abdullah (International Journal of Communication Networks and Information Security (IJCNIS), 2022)
In recent years, chaos studies have been developing tremendously. The importance of using chaos is its deterministic nature. Though the chaos is interpreted as random in nature but it is deterministic. This is a very useful aspect that can be used in encryption of signals. In this paper, the very well-known Chua’s circuit is used to generate random sequences based on initial conditions. These sequences are going to be used for encrypting and decrypting an image. The key is going to be encrypted using a function with a modulus operation then used as an initiation for Chua circuit. The output of Chua circuit is three arrays X, Y, and Z. The process can be divided into two steps. First, one of these sequences is going to be used to form 2D array and the other two sequences also form another 2D array where both have the same size. Then, it is going to be XORed with the image and then the rows and the columns are going to be swapped horizontally and vertically. Second, the other matrix coming from X-Y arrays after mod operation is going to be used as an index for the first processed image. Simulation results show that the scheme sensitivity and complexity to such factors. The importance of this method is that it has plenty of factors that can be unique during generating of these chaotic sequences which makes it very difficult to decrypt the message.